Pendekatan Ma’rifah dan Maḥabbah dalam Proses Pembelajaran Aqidah Akhlak Madrasah Ibtidayah (MI) - Herman (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
This article concludes that the ma'rifah and mahabbah approach in the process of teaching and learning aqeedah morals Madrasah Ibtidaiyah (MI) can construct ideas, ideas, thoughts and formulation of the concept of knowledge to God (ma'rifah) to the level of finding love (mahabbah) deep and eternal into deep recesses of the heart for human life. This study uses a library method or approach (library research), with data collection techniques by examining and exploring several journals, books, and other documents deemed relevant to the study. The ma'rifah approach can be carried out through the takhalli model, the tahalli model and the tajalli model, while the mahabbah approach is through the mahabbatul ‘worship model, the al-maḥabbah fillah model (love for God), and the aṭ-ṭabi’iyyah (natural love) model. DOI: https://doi.org/10.5281/zenodo.3467765